Foliar Application of Silicon: An Innovative and Effective Strategy for Enhancing Tomato Yield in Hydroponic Systems - Raoudha Baioui; Rabaa Hidri; Slim Zouari; Mounir Hajji; Mohamed Falouti; Farah Bounaouara; Moufida Borni; Ahmed Hichem Hamzaoui; Chedly Abdelly; Walid Zorrig; Inès Slama (Agronomy, 2025)
Hydroponic cultivation offers a promising solution to water scarcity by using less water than traditional soil-based agriculture. Although the integration of silicon (Si) in hydroponic systems is still limited, its foliar application is crucial for optimizing plant growth, enhancing resilience, and improving productivity. Therefore, this study aims to explore the effects of silicon foliar application on growth, yield parameters, and photosynthetic activity of one of the most important fruit vegetables worldwide—tomatoes (Solanum lycopersicum L.)—cultivated in a closed hydroponic system. Tomato plants were subjected to a weekly silicon foliar spray (1 mM Na2SiO3) over a period of 10 weeks. Our results demonstrate that silicon foliar spray in hydroponically grown tomatoes significantly improved photosynthetic pigment concentration and enhanced the photochemical efficiency of the photosystems, particularly the quantum yields Y(I) and Y(II). Moreover, silicon treatment resulted in reduced energy dissipation within the photosystems, as indicated by decreases in Y(NPQ), Y(NO), and Y(ND), along with enhanced oxidation of PSI (P700ox). These physiological improvements were directly linked to increased stem width and length, and a substantial boost in plant dry weight compared with untreated controls. Consequently, the silicon foliar spray resulted in a significant increase in the number of racemes, flowers, and fruits. Ultimately, these enhancements culminated in a 69% increase in fruit biomass yield (r2 = 0.70; p < 0.01), highlighting the positive impact of silicon on tomato productivity in hydroponic systems. These findings suggest that silicon foliar application optimizes growth and photosynthetic efficiency while reducing energy dissipation. Consequently, silicon supplementation enhances tomato productivity in hydroponic systems, offering a promising solution for increasing yields in water-efficient agriculture.